Realitas Virtual Dan Penelitian Pendidikan Dasar: Tren Saat Ini dan Arah Masa Depan - Sulaiman Kurdi, Musyarrafah (Lembaga Pengembangan Kinerja Dosen, 2021)
This research explores the utilization of virtual reality (VR) in educational settings and examines current trends, future directions, benefits, and challenges associated with its implementation. The purpose of this library research is to provide an overview of the existing literature on VR and educational research, highlighting the potential of VR technology to enhance traditional teaching methods and improve student engagement, motivation, and learning outcomes. The method used for this research is a comprehensive review and analysis of relevant scholarly articles, books, and reports from academic databases and libraries. The results indicate that VR has been utilized in educational research to create immersive and interactive learning experiences, personalize instruction, bridge the gap between abstract concepts and concrete understanding, and foster critical thinking and problem-solving skills. VR also presents challenges such as cost, accessibility, curriculum integration, teacher training, technical limitations, health and safety concerns, privacy, and ethics. However, the research concludes that with careful planning, adequate resources, and proper support, VR has the potential to revolutionize education and prepare students for a technologically advanced future. Further research and innovation in areas such as immersion, AI integration, collaboration, assessment, accessibility, and ethics are recommended to fully leverage the benefits of VR in educational settings.